INTEGRATING SPEAKING SKILLS BY LISTENING - Ropiyeva, Gulzoda (Журнал иностранных языков и лингвистики, 2023)
Speaking and listening skills have been regarded as being too difficult to cope with ,so generally students arenot willing to participate in tasks focusing on these two skills. When they are integrated through information-gaptasks, students might see the actual outcome and become more willing to practice to achieve more success incommunicating their ideas. Some instructors do not prefer information-gap tasks thinking that the class may get outof control which may cause barriers in communication process.